A Formative Evaluation of The Implementation of The K to 12 English Program of Public Elementary Schools - Ramos, Andy B.; Ulep, Johnrell P. (Future Science / FSH-PH Publications, 2023)
The scope of the K–12 program's implementation of the Language Arts and Multiliteracies Curriculum was investigated by means of the curriculum's design, content, techniques, and approaches, as well as its resources and facilities for learning and evaluation. Quantitative and qualitative research designs were used in the study. Twenty (20) teachers and administrators, along with 226 elementary school pupils, participated in the data collection. The results showed that the English program for grades 6 through 12 was widely implemented. Learning facilities and resources were noted as a major issue. The issues with teachers' and students' readiness and preparation were of a relatively significant nature. As a result, the issues in the remaining areas, such as those with teaching strategies and techniques and curriculum enhancement, were a little more significant. The degree of implementation and achievement level have been proven to be significantly correlated. Therefore, even though the overall mean score indicated a passing rate, the lack of resources and facilities contributed in some measure to the achievement test result showing a sizable portion of students did not fulfill the norm. The Department of Education should therefore give immediate attention to resources and facilities since they are the most pressing issue affecting how the curriculum is implemented.